PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, KUALITAS LAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada CV. Matahari Pink Inspiration Madiun) - Guntur Adhi Prabowo (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2015)
This study aims to determine the effect of Price, Product Quality, Purchasing and Quality Promotion both partially and simultaneously on purchasing decisions on the CV. Matahari Pink Inspiration Madiun.The population in this study are all Consumers who use the printing services in the CV. Matahari Pink Inspiration Madiun total of 100 consumers. The sampling technique is done by using saturated sampling, in order to obtain a sample of 100 respondents. The type of data used are primary data questionnaire data collection methods. Methods of data analysis used multiple regression test. The results showed that partially, the price has a significant positive influence on purchase decisions in this matter because of the price of printing CV Matahari Pink Inspiration showed better quality compared to prices in other printing, product quality has a significant positive influence on purchasing decisions because it has raw materials are of good quality, service quality has a significant positive influence on purchasing decisions because this is the CV. Matahari Pink Inspiration officers provide services properly and quickly, and the promotion has a significant positive influence on purchase decisions this is due to the promotion of CV Matahari Pink Inspiration through billboards, posters, brochures and other - other so that consumers are interested in using  CV. Matahari Pink Inspiration products. Simultaneous research results show that price,